Pragmatic, randomized, blinded trial to shorten pharmacologic treatment of newborns with neonatal opioid withdrawal syndrome (NOWS) - Adam Czynski; Abbot Laptook; Abhik Das; Brian Smith; Alan Simon; Rachel Greenberg; Robert Annett; Jeannette Lee; Jessica Snowden; Claudia Pedroza; Barry Lester; Barry Eggleston; et al. (Trials, 2023)
Abstract Background The incidence of maternal opioid use in the USA has increased substantially since 2000. As a consequence of opioid use during pregnancy, the incidence of neonatal opioid withdrawal syndrome (NOWS) has increased fivefold between 2002 and 2012. Pharmacological therapy is indicated when signs of NOWS cannot be controlled, and the objective of pharmacological therapy is to control NOWS signs. Once pharmacologic therapy has started, there is great variability in strategies to wean infants. An important rationale for studying weaning of pharmacological treatment for NOWS is that weaning represents the longest time interval of drug treatment. Stopping medications too early may not completely treat NOWS symptoms. Methods This will be a pragmatic, randomized, blinded trial of opioid weaning to determine whether more rapid weaning, compared to slow wean, will reduce the number of days of opioid treatment in infants receiving morphine or methadone as the primary treatment for NOWS. Discussion The proposed study is a pragmatic trial to determine whether a rapid-weaning intervention reduces the number of days of opioid treatment, compared to a slow-weaning intervention, and we powered the proposed study to detect a 2-day difference in the length of treatment. Hospitals will be able to use either morphine or methadone with the knowledge that we may find a positive treatment effect for both, one, or neither drugs. Trial registration NCT04214834. Registered January 2, 2020.